Exploring the Integration of Internet in Teaching and Learning of Hospitality Courses at Technical and Vocational Education and Training (TVET) Colleges in Gauteng - Dlamini, Gcebile Delcy (University of the Witwatersrand, Johannesburg, 2024)
spread of internet in the world has brought about a transformation in almost all spheres of life, including the teaching and learning (Nazan Dogruera R. E., 2011). Internet launched a quick and efficient way to access information, which people use for social, entertainment and educational purposes. When technology transformed the hospitality industry, TVET Colleges were forced restructure their curriculum by integrating technology to produce relevant skills that align with industry needs (Mohammed, 2015 ). This study is a qualitative study designed to explore lecturer’s integration of internet to enhance competency based training in Hospitality in a Gauteng Technical and Vocational Education and Training College. The study used the Technology Andragogy Work Content Knowledge (TAWOCK) model to probe lecturer’s effective integration of internet in Hospitality. The study explored the use of internet in teaching and learning in TVET colleges’ in hospitality subjects. The researcher chose Hospitality lecture’s in the Gauteng region, conducting online one on one interviews on Microsoft teams and follow up phone interviews. The Covid-19 pandemic brought a sudden enforcement of the internet integration and general use of technology in Hospitality studies. Lecturers use technology as a supplementary tool for teaching and learning, with very minimal effective integration in teaching and learning. Currently the internet is used for lesson preparation, communicating with students and colleagues, record keeping and sometimes for research in the classroom. Lecturers lack knowledge and information affordances of internet for teaching and learning as well as technology integration skills and knowledge into teaching and learning.in Hospitality. Recommendation of the study have been to explore the department of higher education’s role in technology integration in TVET Colleges and impact of technology on employee’s skill post Covid-19 pandemic. The study was carried out in the midst of the Covid-19 pandemic, where all TVET Colleges in Gauteng implemented emergency teaching and learning which utilizes internet.
A research report submitted in fulfillment of the requirements for the Master of Education, In the Faculty of Humanities, Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Technology Intergration; TVET education; Hospitality Lecturers; SDG-4: Quality education